Handbook of wireless local area networks : - Ilyas, Mohammad (Taylor & Francis, 2005)
Handbook of Wireless Local Area Networks: Applications, Technology, Security, and Standards captures the current state of wireless LANs, and serves as the single comprehensive reference on the subject. Addressing challenges related to the further development of WLAN technology, the Handbook covers the entire spectrum of topics from basic concepts to research grade material. Consisting of 25 articles contributed by expert authors from around the world, the Handbook begins with a detailed introduction that provides an overview of LAN technologies, performance, security, and security protocols. It then delves further into WLAN technology, covering space-time processing, WLAN and cellular convergence, and a peer-to-peer approach to roaming, along with other topics. The Handbook continues by exploring WLAN applications, followed by an extensive discussion of security that includes security issues and the steps that can be taken to minimize WLAN security risks. This text concludes with an analysis of standards, describing 3G UMTS - IEEE 802.11b internetworking and security. ---------------------Features--------------------- · Offers a thorough introduction to LAN technology, performance, security, and security protocols · Analyzes WLAN applications including mobile commerce and innovative medical deployments · Discusses internetworking via 3G UMTS - IEEE 802.11b WLAN · Explores security in IEEE 802.11 WLANs